Validation of the Psoriasis Symptom Inventory (PSI), a patient-reported outcome measure to assess psoriasis symptom severity. (October 2013) - Bushnell, Donald M.; Martin, Mona L.; McCarrier, Kelly; Gordon, Kenneth; Chiou, Chiun-Fang; Huang, Xingyue; Ortmeier, Brian; Kricorian, Gregory
: Background: The objective of this study was to evaluate the measurement properties of the Psoriasis Symptom Inventory (PSI), an eight-item patient-reported outcome measure for assessing severity of plaque psoriasis symptoms. Methods: In this prospective, randomized study using data from adults with moderate-to-severe plaque psoriasis, patients completed the PSI, Dermatology Life Quality Index (DLQI), SF-36v2 Acute, and Patient Global Assessment (PtGA). PSI construct validity was assessed using Spearman rank correlations between PSI and DLQI and SF-36; test-retest reliability and sensitivity to change were evaluated using PtGA as an anchor. Daily 24-h and weekly 7-day PSI versions were evaluated. Results : Eight US sites enrolled 143 patients; 139 (97.2%) completed the study. All symptoms (itch, redness, scaling, burning, cracking, stinging, flaking, and pain) were reported across all response options (not at all severe, mild, moderate, severe, very severe). Test-retest reliability was acceptable (intraclass correlation coefficients range = 0.70–0.80). A priori hypotheses of convergent and discriminant validity were confirmed by correlations of PSI with DLQI items and SF-36 domains. The PSI demonstrated good construct validity and was sensitive to within-subject change ( p < 0.0001). Conclusions : The PSI is brief, valid, reproducible, and responsive to change and has the potential to be a useful PRO measure in psoriasis clinical trials.